Assessment of bleeding in eye surgery. - Tackley, R M (1985)
A new method for assessing microhaemorrhage in eye surgery was used in 16 patients for cataract extraction. It was shown that bleeding was greatest in the first five minutes and that it correlated with the surgeon's clinical estimate of blood loss. The method was used to assess the effect of two different general anaesthetic induction regimens on intraoperative bleeding.